Bringing a knife to a gunfight: A coherent consulting philosophy might not be enough to be effective in professional soccer - Larsen, C. H. (Journal of Sport Psychology in Action, 2017)
Professional soccer is big business and high politics. The primary concern of professional clubs is achieving good results and winning the next game. Integrating sport psychology is a lengthy process, and in order to succeed in professional sports, there is a need for a stable environment. For practitioners to be effective in professional sports organizations, they need to understand various levels of organizational culture. This article provides an overview of a sport psychology program in a Danish professional soccer club and personal experiences, as well as professional reflections on integrating self-reflexivity and cultural sensitivity into the practitioner's philosophy.